BASALT FIBER AS A COMPONENT FOR MICRO REINFORCEMENT OF CEMENT COMPOSITES - Askarov Bakhtiyor Askarovich (Scholar Express Journal, 2021)
The experience of basalt fiber application in the construction industry is summarized. Researches of physical and mechanical and corrosion properties of basalt fiber have been done. The paper describes physical-mechanical and corrosive properties of basalt fiber obtained by different technologies. The perspectives of development and application of basalt fiber have been determined.
Keywords: Basalt fiber; cement stone; corrosion resistance; micro reinforcement